2006
DOI: 10.1080/15257770600894527
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Ki67 and Thymidylate Synthase Expression in Primary Tumour Compared with Metastatic Nodes in Breast Cancer Patients

Abstract: Breast cancer is a heterogeneous disease, so therapeutic predictive biological markers need to be identified. To date an accurate evaluation of predictive markers is mainly done at the primary site; however, the main goal of adjuvant therapy for breast cancer is the control of micrometastases. The aim of this study is to assess as therapeutic and/or prognostic marker, the proliferation status of primary tumors and involved nodes as measured by Ki67 and thymidylate synthase (TS) expression, in 30 breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In breast and colorectal cancer, higher Ki67 expression in primary tumours compared with nodal and liver metastases respectively, was shown [23], [24], [25], [26]. However, in GIST and bladder tumours, as well as other studies of breast and colorectal carcinoma, the converse or no difference in expression has been demonstrated [27], [28], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…In breast and colorectal cancer, higher Ki67 expression in primary tumours compared with nodal and liver metastases respectively, was shown [23], [24], [25], [26]. However, in GIST and bladder tumours, as well as other studies of breast and colorectal carcinoma, the converse or no difference in expression has been demonstrated [27], [28], [29], [30].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this fact, there are concerns about the method reliability because of tumor heterogeneity [18]. In addition, tissue microarray technology is considered to be valid only for primary tumor samples and not for axillary lymph node metastases [19]. …”
Section: Detection Of Ki67mentioning
confidence: 99%
“…While studies have reported a decrease in proliferation markers, e.g. breast and esophageal carcinoma lymph node metastases [ 28 , 29 ], others suggested that metastases are more proliferative than matched primaries, e.g. omental ovarian cancer metastases [ 30 ].…”
Section: Discussionmentioning
confidence: 99%